Enhancing organizational effectiveness through internal communication: a theoretical exploration of channel expansion theory - Obinna, Princewill Iwueke; De Costa, Feroz; Kasimon, Diyana Nawar (Quantum Academic Publisher, 2024)
This conceptual paper delves into the augmentation of organizational effectiveness through internal communication with specific focus on the Channel Expansion Theory. Consequently, organizations strive to enhance their overall effectiveness by diversifying and broadening their array of communication channels for stakeholders’ satisfaction and organizational excellence. While the theory highlights the influence of experiences on channel richness and the importance of prompt feedback, its practical application faces challenges across different organizational contexts, influenced by industry, size, and culture. Besides elucidating the foundational tenets of the theory, this paper provides a nuanced comprehension of communication dynamics within organizational contexts. In high power distance culture like Nigeria, the paper scrutinizes how expanded communication channels empower employees voice while concurrently reinforcing internal communication strategies. Against the backdrop of existing research which underscores impediments to internal communication in Nigerian firms by attributing hindrance to internal communication to corporate politics, hierarchical structures, centralized communication, technological gaps, and power distance cultural disparities. To address these impediments, the paper advocates for further research on power dynamics and hierarchies in organizational setting as well as how channel expansion can mitigate arbitrary managerial powers to ensure the intended goals and purposes of channel expansion are achieved while also ensuring organizational listening.